DIRECTING A SHORT FILM ABOUT EARLY ADULTS WHO ARE EXPERIENCING A QUARTER LIFE CRISIS PHASE TITLED "BREATHE" - Vidyavinaya, Gde Vikranta; Fiandra, Yosa; Rahadianto, Irfan Dwi (eProceedings of Art & Design, 2024)
Quarter life crisis is a crisis that experienced by early adults in the age range of 21-30. This crisis is caused by many factors, namely, financial, career, family, romance, etc. This problem occured due to the unpreparedness of individuals in this transitional phase due to a lack of experience, so early adults often feel stuck and overthinking. Therefore, the writer has the idea to make a short film as the main media in conveying and providing an outlook on overcoming this quarter life crisis in a way that can be said to be trivial. Breathing is not just an ongoing process of life, but also for self-control. Keywords: quarter life crisis, early adults, short film, breathe.